GLOBAL ATTRACTORS TO THREE-DIMENSIONAL NAVIER-STOKES EQUATIONS WITH DAMPING AND FINITE DELAYS - Thi Thuy, Le (HNUE Journal of Science: Journal of Natural Sciences, 2025)
The asymptotic behavior of solutions to the three-dimensional NavierStokes equations is a longstanding and challenging open problem, which has seen numerous important contributions in recent years. In this paper, we consider the NavierStokes equations with damping and delay terms on a bounded domain \( Ω R^3 \). Using the energy method, we prove the existence of global attractors, thus establishing the long-time stability and compactness of the solution set for this class of delayed fluid dynamic models.